Primary glomerular disease with extraglomerular vascular osmiophilic deposits. Issue 6 (June 1972) - Nagi, A. H.; Alexander, F.; Lannigan, R.
Abstract : The ultrastructural changes in renal arterioles and capillaries from three cases of epimembranous nephropathy, one case of minimal change, and one case of minimal change with mild focal proliferation are presented. In addition to the usual subepithelial deposits on the glomerular capillary basement membranes in the cases of epimembranous nephropathy, osmiophilic granular deposits were observed on the outer aspect of extraglomerular vascular basement membranes. No clinical history of hypertension was obtained and there was no histological evidence of renal hypertensive vascular disease.